Estimation of Functional Brain Connectivity - Tenev, Aleksandar; Delev, Tomche; Madjarov, Gjorgji; Gjorgjevikj, Dejan (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2012)
This article presents an overview about the basis of estimators of connectivity, such as Directed Transfer Function (DTF) and Partial Directed Coherence (PDC), their differences and their applicability in the estimation and analysis of functional brain connectivity.